(untitled) (American Journal of Islam and Society, 2013)
In his Religion and Revolution: Spiritual and Political Islam in Ernesto Cardenal, John Morrow has manifested his years-of-research incorporated knowledge in Hispanic, Native American, and Arabic-Islamic studies to shed light on two poorly understood themes – both in the East and, particularly, in the West – via a specific narrative. The themes are, broadly speaking, those of Sufism and the Islamic Republic of Iran. The narrative is the story of Reverend Father Ernesto Cardenal, a Nicaraguan revolutionary Christian priest who had progressively acquired some spiritual and revolutionary interests in Islam after visiting certain Middle Eastern countries, especially Iran. Whether Cardenal is seen as merely a medium for Morrow to express his own findings on Sufism and Iran or as an end in itself is up to the reader. Either way, Morrows’ on-the-whole impartial and unbiased interpretation of Islam, Sufism, and Iran, indirectly through the personality and writings of Cardenal, constitutes a calibre of work rarely seen or read in the western media and literature. This is mostly due to its seemingly close, albeit academic, sympathy with elements of Iran’s right “conservative” and “hardline” elite. Perhaps that is why, at times, one feels that the author has stepped up his defence a shadow too much. The manner he has raised and evaluated some of the data he presents, as well as some of the rumours – against Sufism and especially Iran – he refutes, clearly demonstrates that he has explored and gained access to (1) the pristine image of Sufism and notable Sufis and ...